2003
DOI: 10.1021/ja035253h
|View full text |Cite
|
Sign up to set email alerts
|

Structural Chemistry of “Defect” Cyanometalate Boxes:  {Cs⊂[CpCo(CN)3]4[Cp*Ru]3} and {M⊂[Cp*Rh(CN)3]4[Cp*Ru]3} (M = NH4, Cs)

Abstract: A series of heptametallic cyanide cages are described; they represent soluble analogues of defect-containing cyanometalate solid-state polymers. Reaction of 0.75 equiv of [Cp*Ru(NCMe)3]PF6, Et(4)N[Cp*Rh(CN)3], and 0.25 equiv of CsOTf in MeCN solution produced (Cs subset [CpCo(CN)3]4[Cp*Ru]3)(Cs subset Rh4Ru3). 1H and 133Cs NMR measurements show that Cs subset Rh4Ru3 exists as a single Cs isomer. In contrast, (Cs subset [CpCo(CN)3]4[Cp*Ru]3) (Cs subset Co4Ru3), previously lacking crystallographic characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 58 publications
3
28
0
Order By: Relevance
“…The interaction between the MeCN protons and the cyanide linkers of the cage framework was previously indicated with the solid-state structure of CsʚCo 4 Ru 3 . [2] Labeling studies provided further evidence that the CsʚCo 4 Ru 3 cage undergoes partial disassembly in solution. Two Ru-N bonds must break to dissociate a "rim" CpCo(CN) 3 -did not increase the rate vertex exchange, suggesting that vertex exchange is dissociative, being dependent only on [CsʚCo 4 Ru 3 ].…”
Section: Solution Properties Of the Csʚco 4 Ru 3 Metallo-ligandmentioning
confidence: 93%
See 1 more Smart Citation
“…The interaction between the MeCN protons and the cyanide linkers of the cage framework was previously indicated with the solid-state structure of CsʚCo 4 Ru 3 . [2] Labeling studies provided further evidence that the CsʚCo 4 Ru 3 cage undergoes partial disassembly in solution. Two Ru-N bonds must break to dissociate a "rim" CpCo(CN) 3 -did not increase the rate vertex exchange, suggesting that vertex exchange is dissociative, being dependent only on [CsʚCo 4 Ru 3 ].…”
Section: Solution Properties Of the Csʚco 4 Ru 3 Metallo-ligandmentioning
confidence: 93%
“…The centuries old field of metal cyanide chemistry [1] has experienced a renaissance due the zeolitic, [2,3] magnetic, [4] and electronic properties [5] of cyanometalate materials. Parallel to these application-driven studies, we have focused on synthetic methodologies leading to discrete molecular architectures that can be characterized in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Significant distortions of the cage 3 allow for formation of the pseudocubic structure from octahedral and tetrahedral corners; these occur at the 12 unique Fe-N"C angles around four coordination Fe sites. This distortion is present at each of the four coordination Fe sites to 166.3 (9)°. An examination of the cube body diagonals reveals a slight compression along one of the C 3 axes, which lowers the overall symmetry of the cage.…”
mentioning
confidence: 96%
“…Polymerization could be thus inhibited, and a family of cages with a box-like architecture results. Some early examples showed that the reaction of fac À LMðCNÞ nÀ 3 with LMðH 2 OÞ mþ 3 or LMðMeCNÞ mþ 3 resulted in cyanometallate boxes, ½M 8 ðCNÞ 12 4ðnÀmþÞ , from the displacement of the labile MeCN or H 2 O ligand [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. As part of our interest in this area, we are focusing on the coordination complexes of iron, which have the same components as classic Prussian blue materials and will offer the potential for comparison with classic Prussian blue materials.…”
mentioning
confidence: 99%
“…A single resonance was observed for both solutions with chemical shifts of 0.003 and 7.291 ppm (relative values), respectively. The small chemical shift difference suggested that weak interactions occur between Cs + ions and TG in CD 3 CN, because strong interactions between cesium ions and ligands will cause 133 Cs NMR resonance a large downfield shift [32].…”
mentioning
confidence: 99%